Replication Study of Baron (2022): School Spending and Student Outcomes - Tahreen Zahra; Louis-Philippe Beland (Institute for Replication (I4R), 2023)
Baron (2022) explores the independent effects of operational expenditure and capital expenditure on student outcomes in school districts across Wisconsin from the outcomes of close referendum approvals. By utilizing a dynamic regression discontinuity framework and cubic specification, the author finds that narrowly passing an operational referendum, increases operational expenditure per pupil by 298 each year on average, following the referendum over a ten year period. From this 198 are spent on instructional expenses. These point estimates are statistically significant at the 10% and 5% level, respectively. We first reproduce the main results from the paper without any issues arising. Secondly, we conduct a robustness replicability to (1) dropping school districts from the top and bottom 5% of the revenue limits distribution, categorically, and (2) dividing the time frame of the study into two periods: 1996-2005 and 2005-2014. We find that dropping the top 5% of the school districts by revenue limits reduces the additional operational expenditure by 140 per pupil (lower by 50 percent) and the effects of passing an operational referendum were nearly double in the former period compared to the latter period. Lastly, we find that the estimated effects on student outcomes rely heavily on recent observations.
Keywords: 330